The poison jungle - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire, 2021)
Sundew's mission is to destroy the HiveWings in revenge for nearly wiping out the LeafWings and stealing all the trees from Pantala. The remaining LeafWings are hiding in the few trees that are left in the deadly Poison Jungle. They needs someone like Sundew who can bring down the Hives. However, when their plans are set into motion and war begins, they discover that the jungle is keeping dark secrets, one of which has the power to destroy them all.